Toward a Reversible Consolidation of Paper Materials Using Cellulose Nanocrystals - Operamolla, Alessandra; Mazzuca, Claudia; Capodieci, Laura; Di Benedetto, Francesca; Severini, Leonardo; Titubante, Mattia; Martinelli, Andrea; Castelvetro, Valter; Micheli, Laura (ACS applied materials & interfaces, 2021)
An innovative consolidation strategy for degraded paper is presented based on the reversible application of cellulose nanocrystals as sustainable fillers to reinforce mechanical properties and resistance to further degradation. The compatibility and efficacy of the proposed consolidation treatment are assessed first on pure cellulose paper, used as a model, by reliable techniques such as field emission scanning electron microscopy, atomic force microscopy, tensile tests, X-ray powder diffraction, and Fourier transform infrared spectroscopy, evidencing the influence of the surface functionalization of nanocellulose on the consolidation and protection effects. Then, the consolidation technique is applied to real aged paper samples from Breviarium romanum ad usum Fratrum Minorum S.P. (1738), demonstrating the promising potential of the suggested approach. Amperometric measurements, carried out with a smart electrochemical tool developed in our laboratory, demonstrate the reversibility of the proposed treatment by removal of the nanocrystalline cellulose from the paper surface with a suitable cleaning hydrogel. This completely new feature of the consolidation treatment proposed here satisfies a pivotal requisite in cultural heritage conservation because the methodological requirement for the ″reversibility″ of any conservation measure is a fundamental goal for restorers. A paper artifact, in fact, is subject to a number of natural and man-made hazards, inducing continuous degradation. With time, monitoring and consolidation actions need to be often performed to ensure conservation, and this tends to modify the status quo and compromise the artifact integrity. Removable treatments can potentially avoid erosion of the artifact integrity.